Community Pharmacists' Attitudes and Practice in the Management of Minor Ailments - Mikhael, Ehab Mudher (Iraqi Journal of Pharmaceutical Sciences, 2021)
This study aimed to know the attitudes and practice of pharmacists regarding the management of minor ailments in Iraqi community pharmacies. A cross-sectional study for 320 community pharmacists was conducted during February 2020 using a newly developed and validated questionnaire. Only 4.4% of pharmacists prefer not to deal with minor ailment cases. Minority (15.6%) of participated pharmacists refer more than half of minor ailment cases they face to the physician. Regarding the assessment of minor ailments using WWHAM technique, what are the symptoms are the most commonly asked questions by pharmacists. Only 49.1% mentioned that they ask all WWHAM questions. On the other hand, most pharmacists (90%) educate their patients about the dosing regimen. Meanwhile, less than 10% of pharmacists provide their patients with all possible information about their medications. All demographic factors had no effect on the pharmacists' usage of WWHAM technique and in pharmacist's role in patient counseling or education. In conclusion minor ailment services that provided by community pharmacists' in Iraq was poor at which most pharmacists don't use WWHAM technique appropriately and also fail to provide their patients with the required medication counseling and education.